Frequency and predictors of symptomatic intracranial hemorrhage after intravenous thrombolysis for acute ischemic stroke in a Brazilian public hospital - Cougo-Pinto, Pedro Telles (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2012)
OBJECTIVE: Scarce data are available on the occurrence of symptomatic intracranial hemorrhage related to intravenous thrombolysis for acute stroke in South America. We aimed to address the frequency and clinical predictors of symptomatic intracranial hemorrhage after stroke thrombolysis at our tertiary emergency unit in Brazil. METHOD: We reviewed the clinical and radiological data of 117 consecutive acute ischemic stroke patients treated with intravenous thrombolysis in our hospital between May 2001 and April 2010. We compared our results with those of the Safe Implementation of Thrombolysis in Stroke registry. Univariate and multiple regression analyses were performed to identify factors associated with symptomatic intracranial transformation. RESULTS: In total, 113 cases from the initial sample were analyzed. The median National Institutes of Health Stroke Scale score was 16 (interquartile range: 10-20). The median onset-to-treatment time was 188 minutes (interquartile range: 155-227). There were seven symptomatic intracranial hemorrhages (6.2%; Safe Implementation of Thrombolysis in Stroke registry: 4.9%; p = 0.505). In the univariate analysis, current statin treatment and elevated National Institute of Health Stroke Scale scores were related to symptomatic intracranial hemorrhage. After the multivariate analysis, current statin treatment was the only factor independently associated with symptomatic intracranial hemorrhage. CONCLUSIONS: In this series of Brazilian patients with severe strokes treated with intravenous thrombolysis in a public university hospital at a late treatment window, we found no increase in the rate of symptomatic intracranial hemorrhage. Additional studies are necessary to clarify the possible association between statins and the risk of symptomatic intracranial hemorrhage after stroke thrombolysis.